Cortisol salival, perfil psicológico y trastornos temporomandibulares en pacientes con enfermedad renal crónica en hemodiálisis - Vieira, Cleide Dejaira Martins; Vieira, Caroline Martins; Moreira, Paulo Ricardo; Winkelmann, Eliane Roseli; Krug, Rodrigo de Rosso (Lecturas: Educación Física y Deportes, 2025)
The objective was to verify the level of salivary cortisol, the psychological profile and the presence of Temporomandibular Dysfunction (TMD) in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD). This was a cross-sectional study, carried out with 18 patients with a mean age of 60.39 years, the majority of whom, 83.33%, were male. Patients with a score higher than 19 points on the Mini-Mental State Examination questionnaire and at least one positive response on the American Academy of Orofacial Pain TMD screening questionnaire and who had been undergoing HD for more than 3 months were included. Patients who, during data collection, presented an insufficient amount of saliva for laboratory analysis, who were in isolation or hospitalized were excluded. After analyzing the screening results, patients underwent the research protocol: Questionnaire for collecting clinical and sociodemographic data; Fonseca Anamnestic Index; Hamilton Anxiety Scale; Beck Depression Inventory and cortisol analysis. Fisher’s exact test was applied (p≤0.05). As a result, it was found that most of the patients studied had some degree of TMD (66.67%), symptoms of anxiety (94.44%) and symptoms of depression (55.56%). In 94.44% of the sample, salivary cortisol levels were normal, although 83.33% of the patients perceived themselves as stressed. It was concluded that patients with CKD on HD have some degree of TMD, symptoms of anxiety and depression, however, their salivary cortisol levels are normal, even though the patients perceive themselves as stressed.